2010
DOI: 10.1038/onc.2010.30
|View full text |Cite
|
Sign up to set email alerts
|

Liver X Receptor activation downregulates AKT survival signaling in lipid rafts and induces apoptosis of prostate cancer cells

Abstract: Cholesterol is a structural component of lipid rafts within the plasma membrane. These domains, used as platforms for various signaling molecules, regulate cellular processes including cell survival. Cholesterol contents are tightly correlated with the structure and function of lipid rafts. Liver X receptors (LXRs) have a central role in the regulation of cholesterol homeostasis within the cell. Therefore, we investigated whether these nuclear receptors could modulate lipid raft signaling and consequently alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
170
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(182 citation statements)
references
References 51 publications
11
170
0
1
Order By: Relevance
“…Indeed, Apoe −/− and Abca1/g1 −/− mice were shown to have an increase in cholesterol accumulation within lipid rafts of HSCs, leading to increased signaling through the common β subunit to enhance the production of myeloid cells 37, 38. In contrast, other studies demonstrated that LXR agonist treatment disrupted the localization of key signaling molecules vascular endothelial growth factor receptor 2 and protein kinase B within lipid rafts, suggesting that activation of LXRs decreases the intracellular distribution of cholesterol to the rafts 49, 50. Thus, LXRs may be modulating lipid raft cholesterol content, which indirectly affects the identity and function of EPCs.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Apoe −/− and Abca1/g1 −/− mice were shown to have an increase in cholesterol accumulation within lipid rafts of HSCs, leading to increased signaling through the common β subunit to enhance the production of myeloid cells 37, 38. In contrast, other studies demonstrated that LXR agonist treatment disrupted the localization of key signaling molecules vascular endothelial growth factor receptor 2 and protein kinase B within lipid rafts, suggesting that activation of LXRs decreases the intracellular distribution of cholesterol to the rafts 49, 50. Thus, LXRs may be modulating lipid raft cholesterol content, which indirectly affects the identity and function of EPCs.…”
Section: Discussionmentioning
confidence: 99%
“…15 Many studies have shown that LXR agonists could inhibit cancer cell proliferation by modulating cell cycle protein expression 2,8,9,16 and/or induce cancer cell death, mainly through caspase-3-dependent apoptosis. 5,7 We demonstrate here for the first time that LXR agonist activation of LXRb can induce pyroptotic cell death through an NLRP3 inflammasome-dependent caspase-1 activation pathway. This effect seems to be quite surprising, as many studies report that LXR is mainly a negative regulator of inflammation by downregulating the expression of selective inflammatory genes (e.g., il1b, il6, inos, cox2, mmp9, mcp1, mcp3) through a process that involves DNA interaction, known as transrepression.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been shown that LXR reduces growth of PCa cells and xenografts (56,57), delaying the progression to androgen independence in a xenograft model (58). This has been attributed to cholesterol depletion, which disrupts cholesterol-rich lipid rafts and thus down-regulates Akt activity (57).…”
Section: Discussionmentioning
confidence: 99%